(3fJGFL GdacQ GdeYQH Yf JaGVd GdKeQs - (3GdQheqj, GdUfYGfj, TYHGf Hf Sdje Hf YKeGf, J (B1149 (3g`s
(3ChdgG (B:s
(3HSe Gddg MeOG def CfHJ ChQGb GdTLQ hRGfgG ddBcdjf HGdKeQ (B** (3hNUfG HGdgGTej GdjKQHj fHjfG GdeNJGQ NjQ GdYQH (B** (3hBdg GdCWgGQ NjQ Bd Ydi eeQ GdOgQ hGdJhGdj s
(3BNQgG (B:s
(3hddUOGY GdNGQ aj GdQhS HGdNd ajg ZGjI GdJfajS (B** (3hjRgb GdfaS eY GdCPgGf cTjQL PGc HdG JhGfj (B** (3hGdMeO ddg Ydi GdHdGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3/164s
(3EjVGM Gdecfhf (B2/621s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdRQGYI hGdCYTGHs